Engineering Properties Of Warm Mix Asphalt Incorporating Fly Ash - Lee, Mei Ting (Universiti Sains Malaysia, 2017)
Excessive waste disposal due to the rapid growth in the construction industry is an issue to be solved. Fly ash was introduced in the construction industry to reduce the pollution problems. The performance of warm mix asphalt incorporated fly ash as the mineral filler was evaluated. The service characteristics of the control sample and warm mix asphalt incorporated fly ash was determined using workability index and compaction energy index to indicate the ease which allows producing, handling, placing and compacting of asphalt mixtures. From the results obtained, fly ash shows better workability and compaction energy as compared to the control sample. Analysis of service characteristics and mixture performance of warm mix asphalt incorporated Sasobit (2 % and 4%) and mixed at a different mixing temperature (130˚C and 145˚C) was also important. In order to simulate the actual condition on site after paving, asphalt mixtures with 4% air voids were used to evaluate the engineering properties of asphalt mixtures in term of indirect tensile strength and resilient modulus. The asphalt mixture with higher Sasobit content and mixed at higher temperature found to have a better indirect tensile strength and resilient modulus. Meanwhile, moisture damage was applied to asphalt mixture with 7% air voids using accelerated laboratory vacuum saturator to indicate the actual condition on site. The mixture performance was studied using tensile strength ratio. From the tested results, the performance of the warm mix asphalt shows the inconsistency to moisture susceptibility. Therefore, further studies should be carried out to improve the warm mix asphalt.